PERBANDINGAN NILAI CHART DATUM DARI LIMA VARIASI DATA BERDASARKAN LAMA PENGAMATAN PASANG SURUT AIR LAUT DI STASIUN PASUT JAKARTA - Marantika, Happy Ary Wahyu; Khomsin, Khomsin (Geoid, 2019)
One of the problems that may arise in the development of new marine infrastructure is the unavailability of the datum chart value. So, there is a need for tide observations to determine the value of the datum chart in the area. This study contains a comparison of the value of chart datum from five variations of the length of observation at the tide station of the Geospatial Information Agency (BIG) in Jakarta. The results of this study can be used to consider the efficiency of tidal observations, especially in determining the duration of observation. The value of the chart datum (MSL and LWS) is calculated from the tidal component generated from the harmonic analysis using Matlab. Test the significance of the value of the datum chart in Microsoft Excel. From this study, it can be concluded that a good long-term predictive value of MSL can be obtained from observations for 15 days or 30 days, without the need for long observations of up to one year. While the LWS predictive value is getting better when the observations are made longer. The smallest difference in MSL value on average from each variation of the observation time is 0 meters and the largest is 0,002 meters, with the smallest difference in the average LWS value of each variation of the observation time 0,001 meters and the largest 0,221 meters.